The Impact of the Laos-China Railway Project on Laotian Human Security in 2021-2023 - Denata, Hesti Eka (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
In 2017 until 2020, the economic security of the Laotian society is experiencing problems where the unemployment rate is above 2%. This high unemployment rate affects the slow economic growth of Laos. In December 2021, Laos-China railway project is finally completed after 5 years of construction. In this paper, the author describes the positive and negative impacts caused by this railway project on the human security of Laotian society. In addition, this research also aims to analyze Laos government policies in preventing the negative impacts caused by this project on its human security using descriptive-qualitative research methods. The research found that the positive impacts of Laos' economic policy to cooperate in the railway project with China on its human security such as providing more jobs for Laotian society, increasing state revenue, improving the living standards of Laotian society. However, this project also has a negative impact on the environmental security of Laotian society. The negative impact can be prevented by the Lao government's efforts such as cooperating with China as a cooperation partner. Laos' economic policy in cooperation with China through the railway project greatly affects human security, especially in economic security. Laos succeed to reduce unemployment rate with the Laos-China railway project.